1997
DOI: 10.1111/j.1365-263x.1997.tb00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Infraocclusion of primary molars in monozygotic twins: report of two cases

Abstract: Genetic factors have been implicated in the aetiology of infraocclusion, but only three published reports describe infraocclusion of primary molars in twins. This case report describes the occurrence of infraocclusion in two pairs of twins. The distribution of affected teeth and the severity of infraocclusion were strikingly similar in each pair. The report provides further evidence of a genetic contribution to the aetiology of the condition, and also highlights the need to examine siblings, and especially twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Studies have shown the commonness proportion of infraocclusion in kids being 1.3-8.9% with an equal occurrence in males and females. Nevertheless, this proportion is reported to be between 18.1- 44% in the siblings of those children [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown the commonness proportion of infraocclusion in kids being 1.3-8.9% with an equal occurrence in males and females. Nevertheless, this proportion is reported to be between 18.1- 44% in the siblings of those children [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Submersion is a clinical term describing a tooth depressed below the occlusal plane [ 6 ], as normal vertical tooth eruption appears to be inhibited, therefore, the affected teeth appearing to ‘submerge’ as the adjacent teeth continue to erupt around them [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies [6][7][8][9][10][11][12] have documented its occurrence in monozygotic twins and relatives in kindreds, adding Mendelian evidence to support a likely genetic mechanism underlying the expression of infraocclusion. Further corroboration of genetic etiologic factors comes from studies showing that infraocclusion is an abnormality frequently observed accompanying the presence of other dental anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers believe that a genetic predisposition has a significant influence. They presented monozygotic twins demonstrating remarkably similar patterns of ankylosis to confirm such hypotheses [7].…”
Section: Figure 2 a 19mentioning
confidence: 68%